The Use of Photodynamic Therapy on Medication-Related Osteonecrosis of the Jaws: Animal Study - Karapinar Gökay; Zincir Özge Özdal; Ünür Meral; Olgaç Necat Vakur (Balkan Stomatological Society, 2021)
Background/Aim: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) was first introduced in 2003 and its scope was expanded by the name medication-related osteonecrosis of the jaw (MRONJ), since 2014. This study aimed to evaluate the effects of photodynamic therapy (FDT) on tissue samples by histopathological and histomorphometric examination and serum TRACP-5b (Tartrateresistant acid phosphatase-5b) measurement in rats.